Utilization of coconut shell as a supplementary cementitious material in concrete - Itam Z.; Dzar Johar A.; Syamsir A.; Zainoodin M.; Shaikh Ahmad Fadzil S.M.M.; Beddu S. (Elsevier Ltd, 2023)
Agriculture; Cements; Concrete mixtures; Shells (structures); Testing; Agricultural industries; Building development; Cementitious materials; Coconut shells; In-buildings; Non-renewable; Partial replacement; Research focus; Supplementary cementitious material; Tropical countries; Compressive strength